Metacaspases, Autophagins and Metallocarboxypeptidases: Potential New Targets for Chemotherapy of the Trypanosomiases - Alvarez, Vanina Eder (2013)
During the last decade, de novo drug discovery approaches have come into focus due to the increased number of parasite pathogen genomes sequenced and the subsequent availability of genome-scale functional datasets. In order to prioritize target proteins, these approaches consider traits commonly thought to be desirable in a drug target, including essentiality, druggability (whether drug-like molecules are likely to interact with the target), assayability, importance in lifecycle stages of the pathogen relevant to human health, and specificity (i.e. the target is absent from, or substantially different in, the host). Proteases from protozoan parasites have become popular drug targets since these enzymes accomplish both housekeeping tasks common to many eukaryotes as well as functions highly specific to the parasite life style. Trypanosoma cruzi, the parasitic flagellate, agent of Chagas Disease, contains several cysteine, serine, threonine and metallo proteinases. This review will deal with peculiar families described in this parasite. Among them, two eukaryote homologues of the carboxypeptidases Taq are promising targets due to their particular phylogenetic distribution. Also absent in metazoans, metacaspases are essential peptidases playing important roles in cell growth, death and differentiation of trypanosomatids. Finally, autophagins are involved in the regulation of a conserved degradative pathway, the autophagy pathway, and result important for parasite survival under nutritional stress conditions and differentiation. Although so far there are no specific inhibitors for these families, the increasing knowledge of their biochemical properties, including substrate specificity, crystal structure, and biological functions, is an essential step towards the development of inhibitors.